2018
DOI: 10.1177/0256090918804390
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Publicly Financed Health Insurance Scheme (Rashtriya Swasthya Bima Yojana) from Equity and Efficiency Perspectives

Abstract: Executive Summary Catastrophic health expenses result in impoverishment of a large number of people every year in India. This often forces the resource-poor households to forego treatment due to lack of affordability. Providing quality health care to all at an affordable cost is a policy commitment for India as it is a signatory of the Alma Ata Declaration. The Government of India is working towards providing universal health coverage through its National Health Policy. As part of universalization of health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 15 publications
0
27
1
Order By: Relevance
“…The effect of RSBY on impoverishment was not clear as one study reported that RSBY had no effect on impoversihment, 16 whereas another study reported an increase in impoverishment among the Above Poverty Line (APL) housholds. 25 Box…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of RSBY on impoverishment was not clear as one study reported that RSBY had no effect on impoversihment, 16 whereas another study reported an increase in impoverishment among the Above Poverty Line (APL) housholds. 25 Box…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Four studies 14 16 19 25 provided information on the effect of RSBY on CHE, the RSBY households were less likely to incur CHE for outpatient care, inpatient care and overall CHE. It was observed that beneficiaries of the scheme reported a reduction in CHE; however, one study 25 reported that there was no effect of RSBY on CHE. According to Azam, 14 the effect was same for both rural and urban households.…”
Section: Catastrophic Health Expenditure (Che)mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the literature is rife with articles analyzing the effect of the JSY cash transfer program on maternal care [14][15][16], the effect of the public health insurance (RSBY) on MCH service utilization has not been investigated. Studies on RSBY have mainly focused on patterns of enrollment to the insurance scheme, its utilization and effect on outof-pocket expenditure of households [20,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…We used information on women who gave birth both before and after the introduction of the RSBY. RSBY covers maternity bene ts and all expenses related to delivery at the hospital, including transportation charges of 100 rupees paid to the bene ciary [24]. In particular, hospitals will be paid 2500 rupees for natural delivery and 4500 rupees for C-section delivery, but prenatal expenses are not covered under the scheme.…”
Section: Introductionmentioning
confidence: 99%